Optimal subsidy policy for new energy vehicles based on the influence of multiple factors and consumers' green preference - Wang, Yi; Zhang, Zilu; Zhu, Meihong (Managerial and decision economics, 2024)
Policies concerning subsidies for new energy vehicles and consumers' environmental preferences significantly impact the sales of such vehicles. To investigate the correlation between sales and subsidies or consumers' environmental preferences and to devise optimal subsidy strategies, two Stackelberg game models are constructed based on both monopoly and duopoly markets, with solutions derived for Nash equilibrium points. In order to refine the strategy for subsidy adjustments, two dynamic adjustment models considering bounded rationality are established. Additionally, the process of adjusting subsidies towards Nash equilibrium points is analyzed. Simulations, utilizing actual research data, are performed to assess China's current adjustment strategies. The findings reveal a substitution relationship between consumers' environmental preferences and subsidies. Furthermore, optimal subsidy levels and bounded rational subsidy adjustment strategies are identified. Governments should thoroughly consider consumers' environmental preferences when refining subsidy policies, as it is a crucial factor influencing the development of the new energy vehicle industry.